GENERAL PRINCIPLES OF STATE REGISTRATION OF RIGHTS AND THEIR ADMINISTRATIVE AND LEGAL ASPECTS - Nikitin, Volodymyr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of the article is a comprehensive approach to the analysis of theoretical and methodological principles and aspects, normative foundations and practical implementation of the legal principles of state registration of real property rights and their encumbrances. Research methods: the general philosophical dialectical, systematic, formal-dogmatic and comparative-legal method was used. Results: the general legal principles of state registration of property rights to immovable property and their encumbrances were researched, the peculiarities of the general legal principles defined by the legislation and their role in the registration procedure were analyzed, and the need to improve and overcome legal conflicts in the normative legal acts of the specified sphere of activity was established. Discussion: on the basis of a comprehensive analysis of theoretical and legal principles, normative foundations of the application of general legal principles in the field of state registration of property rights to immovable property and their encumbrances, as well as the practical implementation by state registrars of their powers in the field of state registration of property rights to immovable property and their encumbrances, the administrative and legal aspects of the general legal basis of state registration of property rights to immovable property and their encumbrances established by legislation were analyzed.